Stroke survivors' experiences of team support along their recovery continuum - W. Hartford; S. Lear; L. Nimmon (BMC, 2019)
Abstract Background A coordinated stroke rehabilitation care team is considered optimal for supporting stroke survivors from diagnosis to recovery. Despite this recognition, many stroke survivors cannot access essential rehabilitation services. Furthermore, there is a lack of understanding of stroke patients' and their caregivers' rehabilitation needs and wishes. We sought to gain insight into healthcare and social structures from the perspective of patients and caregivers that can better support long-term stroke recovery. Methods We conducted individual interviews with 24 participants comprised of stroke survivors, spousal caregivers, stroke support group coordinators, and speech pathologist. Participants were recruited through three stroke survivor support groups. An empowerment lens was integrated into data analysis and data interpretation. Results Two dominant themes captured participants' experiences through stroke survivors' trajectory of care. 1) Experiences of managing stroke. This theme identified stroke survivors and spousal caregivers' experiences with stroke recovery, rehabilitation, and fulfilling unmet needs. 2) Resources of support. This theme described the social and financial support structures drawn upon to assist with stroke rehabilitation. Conclusions The study highlighted a lack of teamwork between stroke survivors, spousal caregivers, and health professionals. This fragmented care was compounded by inequities in rehabilitation programs and health services resulting in what appeared to be a disempowering rehabilitation process. Although stroke recovery groups were a significant source of support for stroke survivors and spousal caregivers, participants perceived they were overlooked, by stroke recovery healthcare providers, as a site for stroke recovery healthcare services. An empowerment approach to stroke rehabilitation involves collaboration between stroke survivors, caregivers, healthcare providers, health services, and existing community stroke support structures. Framing stroke based care through an empowerment lens may serve to address stroke rehabilitation inadequacies and inequities.